A profiled fiber-reinforced, toughened elastomeric material and its preparation method and use
Patent Information
- Application Number
- CN202510448782.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-10
- Publication Date
- 2026-10-27
AI Technical Summary
第二,应力传递效率低下
[0032]本申请提供了上述的高强度、高韧性橡胶材料在制备轮胎、胶管、减振件、密封件、柔性穿戴件应用。
Smart Images

Figure CN122978540A_ABST
Abstract
Description
Technical Field
[0001] This application relates to a profiled fiber reinforced and toughened elastomer material, its preparation method and application, belonging to the field of rubber material technology. Background Technology
[0002] Modern industry has an increasingly urgent need to upgrade the mechanical properties of rubber materials, especially in key fields such as tires, engineering machinery, and aerospace. Materials must simultaneously meet two core indicators: high strength to maintain structural stability and high toughness to achieve impact resistance and deformation adaptation. Traditional rubber reinforcement technologies mainly rely on rigid particulate fillers or fiber composite systems. While these can improve material rigidity and creep resistance to some extent, they are limited by the interface matching problem between the reinforcement and the matrix, generally resulting in a contradiction where strength and toughness cannot be synergistically improved. Particularly in fiber-reinforced systems, the following technical bottlenecks urgently need to be overcome: First, weak interfacial bonding mechanism. Existing micron-sized cylindrical fibers have smooth surfaces and low chemical activity, mainly bonding with the rubber matrix through physical adsorption, lacking a multi-level mechanical anchoring structure. Under dynamic loads, due to the significant difference in hardness between the fiber and the matrix, stress abrupt changes easily occur at the interface, leading to the initiation of microcracks and their gradual expansion into interfacial debonding. Second, low stress transfer efficiency. The linear structure of traditional fibers means that stress can only be transferred in a single direction, making it impossible to construct a multi-directional energy dissipation network. When external loads are applied to the material, stress is excessively concentrated along the fiber axis, and cracks easily propagate rapidly along the fiber-matrix interface, significantly reducing the material's impact resistance. Third, the end-defect effect is prominent. The abrupt shape change at the ends of cylindrical fibers creates localized high-stress zones, which become the preferred failure point during tensile or tearing processes. In practical applications, such end defects cause premature material failure, severely limiting service life. These problems lead to insufficient reliability of existing fiber-reinforced rubber materials in critical scenarios such as dynamic sealing and impact cushioning. Therefore, it is urgent to overcome the limitations of existing technologies through structural innovation in the reinforcement. Developing nanofiber reinforcement systems with three-dimensional irregular structures, optimizing interfacial stress distribution through geometric design, and constructing multi-level energy dissipation channels have become important research directions for solving the problem of synergistic strength and toughness. Summary of the Invention
[0003] This invention provides a rubber material reinforcement technology based on the design of irregular nanofiber structures. By introducing three types of characteristic nanostructures—gradient diameter fibers, end spherical fibers, and dendritic fibers—a multi-level stress transmission network and energy dissipation mechanism are constructed at the nanoscale, thereby improving the strength and toughness of the rubber material.
[0004] This application provides a high-strength, high-toughness rubber material, comprising, by weight: (a) 100 parts elastomer; (b) 1 to 10 parts of a profiled fiber composition, wherein the profiled fiber composition comprises one or more of gradient diameter fibers, end-spherical fibers, and dendritic fibers, and the profiled fiber composition is dispersed in the elastomer; (c) 0.5 to 4 parts of silane coupling agent; (d) 10~100 parts of filler; (e) 3 to 15 parts of a vulcanizing composition, said vulcanizing composition comprising a vulcanizing agent, a vulcanization accelerator, stearic acid and zinc oxide; (f) 0.5 to 5 parts of antioxidant.
[0005] Gradient-diameter fibers feature a smooth transition in fiber diameter along the axial direction, creating a continuous mechanical gradient that effectively disperses stress concentration within the rubber matrix. Simultaneously, the variable-diameter structure increases the specific surface area, resulting in a gradient distribution of interfacial bonding strength and preventing interfacial debonding caused by sudden localized stress changes.
[0006] The spherical fiber at the end has a spherical or near-spherical structure with a diameter larger than that of the main body at at least one end. This fiber structure has a good anchoring and reinforcement effect. Under load, stress is uniformly transmitted to the main body through the spherical end, avoiding interface failure caused by stress concentration. At the same time, this structure can mechanically block the microcrack propagation path. When the crack extends to the fiber end, the spherical geometry forces the crack propagation direction to deflect, improving fracture toughness.
[0007] Among them, the dendritic fiber forms at least one branch structure during the axial extension of the fiber. This fiber structure has a good three-dimensional network reinforcement effect. When the crack encounters the branch node, the branch structure will force the crack to forcibly branch. At the same time, its multi-level interface generates a synergistic energy dissipation effect, which consumes the energy required for crack propagation, thereby effectively preventing the further propagation of cracks and improving the fracture toughness of rubber materials.
[0008] For gradient diameter fibers, taking wavy fibers and tapered fibers as examples, wavy fibers are fibers with a wavy undulating structure along the fiber axis, while tapered fibers are fibers whose diameter gradually decreases from one end to the other, forming a tapered profile structure. In addition, other fiber morphologies that conform to gradient diameter fibers are also within the protection scope of this application.
[0009] For the end-spherical fibers, the number of end-spherical shapes is not specifically limited; it can be one or two. If there are two, there is one end-spherical shape at each end of the main stem. Furthermore, the shape of the end-spherical shapes is not strictly limited to spherical. Those skilled in the art will understand that spherical shapes or those that can achieve similar effects to the end-spherical shapes in this application should be within the scope of protection of this application.
[0010] For dendritic fibers, the trunk and branches can be distinguished by their length and diameter. In addition, there is no specific limit on the number of branches, but the number of branches must be no less than one. There is also no specific limit on the location of the branches. For example, branches can be formed in the middle of the trunk or at both ends of the trunk. There is also no specific limit on the angle of the branches.
[0011] Optionally, the irregular fiber composition is 2 to 7 parts.
[0012] When the content of the shaped fiber composition is low, the modification effect on the rubber material is small. When the content of the composition is high, it will reduce the resilience and elongation at break of the rubber material to a certain extent, and reduce the improvement effect on the toughness of the rubber material.
[0013] Optionally, the fiber diameter of the shaped fiber composition is less than 1000 nm; Optionally, the fiber diameter of the shaped fiber composition is less than 500 nm; When fiber sizes reach the nanoscale, they exhibit superior performance in enhancing the strength and toughness of rubber matrices. This is because nanofibers possess a higher specific surface area, enabling them to form more favorable interfacial bonds with the rubber matrix. Compared to micron-sized fibers, nanofibers achieve significant modification effects at lower application ratios. Furthermore, the diameter of micron-sized fibers is similar to the size of microcracks within the rubber material, causing crack tips to easily propagate along the fiber interface, thus limiting the improvement in toughness. As fiber sizes further decrease to below 500 nanometers, the constraint effect of the fibers on the rubber molecular chains shifts from "rigid restriction" to "flexible guidance." This change allows the rubber material to maintain good toughness while simultaneously increasing strength.
[0014] Optionally, the fiber diameter of the gradient variable diameter fiber changes smoothly along the axial direction, the fiber diameter changes at a rate of less than 50 nm per hundred nanometers along the axial direction, and the fiber aspect ratio is 5~200. Optionally, the aspect ratio of the gradient diameter fiber is 5~100; The diameter of a gradient variable diameter fiber is the average diameter, which is the average of the maximum and minimum fiber diameters. The fiber length-to-diameter ratio is the ratio of the fiber length to the average fiber diameter.
[0015] If the diameter of the fiber varies greatly in the axial direction, when the rubber composite material is subjected to external force, a large stress concentration will occur at these locations where the diameter changes abruptly during the stress transmission process, thereby weakening the overall modification effect of the rubber material.
[0016] Optionally, the end-spherical fiber includes a main stem and end spherical parts, wherein the aspect ratio of the main stem (excluding the end spherical parts) is 5 to 200, and the diameter of the end spherical parts is 1.2 to 3 times the diameter of the main stem.
[0017] Optionally, the diameter of the trunk changes smoothly along the axial direction, and the rate of change of the trunk diameter within each hundred nanometers along the axial direction is less than 50 nm. Optionally, the aspect ratio of the main stem of the end-globose fiber, excluding the end-globose type, is 5 to 100.
[0018] The diameter of the end-spherical fiber is the average diameter of the main stem excluding the end-spherical type, which is the average of the maximum and minimum diameters of the main stem. The length-to-diameter ratio of the main stem excluding the end-spherical type is the ratio of the length of the main stem to the average diameter excluding the end-spherical type. End-spherical diameter: The fiber diameter is the ratio of the diameter of the end-spherical type to the average diameter of the main stem fiber.
[0019] When the aspect ratio of the end-spherical fiber is too large, it can lead to fiber entanglement during processing, which affects the uniformity of fiber dispersion in the rubber matrix. Furthermore, excessively long fibers are prone to breakage under mechanical shear forces during processing; when the ratio of the end-spherical diameter to the fiber diameter is too large, external stress usually concentrates at the bottom of the end-spherical section, significantly increasing the risk of breakage in that area.
[0020] Optionally, the dendritic fiber includes a trunk and branches, the trunk has an aspect ratio of 10 to 200, the branches have an aspect ratio of 5 to 150, the trunk and branches have a length ratio of 1 to 200, the trunk and branches have a diameter ratio of 1 to 20, the trunk diameter changes smoothly along the axial direction, and the trunk diameter changes at a rate of less than 50 nm per hundred nanometers along the axial direction. Optionally, the aspect ratio of the main stem of the dendritic fiber is 10 to 100; Optionally, the length ratio of the trunk to the branches can be 1 to 100.
[0021] Dendritic fibers are characterized by trunks with larger average diameters and branches with smaller average diameters. When average diameters are the same, the trunk with the larger length is the trunk and the branch with the smaller length. The average diameter is the average of the maximum and minimum fiber diameters. The trunk aspect ratio is the ratio of the trunk length to the average diameter. The branch aspect ratio is the ratio of the branch length to the diameter. The diameter ratio of the trunk to the branches is the ratio of the trunk's average diameter to the branch's diameter.
[0022] When the aspect ratio of the trunk to the branches of dendritic fibers is too high, fiber entanglement can occur during processing, affecting the uniformity of fiber dispersion in the rubber matrix. Furthermore, excessively long fibers are prone to breakage under mechanical shear forces during processing; a high length-to-diameter ratio and a low three-dimensional network reinforcement effect of the fibers result in poorer modification of the rubber.
[0023] Optionally, the gradient diameter fiber accounts for 50-90 wt% of the total amount of the profiled fiber composition; Optionally, the gradient diameter fiber accounts for 60-80 wt% of the profiled fiber composition. The key performance requirement for the rubber material in this scheme is high strength. Therefore, it is necessary to ensure that the rubber material has sufficient strength to reduce the damage caused by external forces. To achieve this goal, a high proportion of gradient diameter fibers is required.
[0024] Optionally, the material of the profiled fiber is one or more of the following: poly(p-phenylene terephthalamide) fiber, polyimide fiber, polyester fiber, polyurethane fiber, poly(m-phenylene isophthalamide) fiber, polyolefin fiber, polyamide fiber, polyacrylonitrile fiber, polyvinyl alcohol formal fiber, polyvinyl chloride fiber, polybenzimidazole fiber, and polytetrafluoroethylene fiber. The polyester fiber includes one or more of polyethylene terephthalate fiber, polybutylene terephthalate fiber, polypropylene terephthalate fiber, and polyethylene naphthalate fiber. The polyurethane fiber includes one or more of polyether polyurethane fiber and polyester polyurethane fiber; The polyolefin fibers include one or more of the following: polyethylene fibers, ultra-high molecular weight polyethylene fibers, polypropylene fibers, poly-1-butene fibers, and halogenated homopolymer / copolymer / halogenated copolymer fibers of ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, and 4-methyl-1-pentene monomers. The polyamide fiber includes one or more of the following: polycaprolactam fiber, polyhexamethylene adipamide, polysaccharide adipamide, polysaccharide adipamide, polydodecanoylhexamethylene adipamide, polyundecanoyl lactam, polydodecanoamide, and polysaccharide adipamide.
[0025] It should be noted that this application does not limit the material of the shaped fiber. In addition to the materials listed above, modified or similar materials based on the above materials or other fiber materials commonly used in rubber products can theoretically be prepared into shaped fibers and achieve the same effect.
[0026] Optionally, the elastomer includes one or more of the following: natural rubber, isoprene rubber, styrene-butadiene rubber, pentadiene rubber, cis-butadiene rubber, butyl rubber, ethylene propylene rubber, fluororubber, acrylate rubber, chlorosulfonated polyethylene, silicone rubber, polyurethane rubber, polyether rubber, and polysulfide rubber. Optionally, the elastomer includes one or more of natural rubber, isoprene rubber, styrene-butadiene rubber, pentadiene rubber, butadiene rubber, cis-butadiene rubber, butyl rubber, and ethylene propylene rubber.
[0027] Optionally, the silane coupling agent includes one or more of vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane, γ-mercaptopropyltrimethoxysilane, bis(γ-triethoxysilylpropyl)tetrasulfide, bis(γ-triethoxysilylpropyl)disulfide, γ-mercaptopropyl(bis-(tridecyl-hexaethoxy)ethoxy)silane, and 3-octanoylthio-1-propyltriethoxysilane; Optionally, the filler is selected from one or more of carbon black, silica, calcium carbonate, talc, kaolin, bentonite, mica, and wollastonite.
[0028] Optionally, the vulcanizing agent is selected from one or more of sulfur, metal oxide vulcanizing agents, or peroxide vulcanizing agents.
[0029] Optionally, the vulcanization accelerator includes one or more of the following: dithiocarbamate vulcanization accelerators, thiuram vulcanization accelerators, thiazole vulcanization accelerators, guanidine vulcanization accelerators, sulfenamide vulcanization accelerators, triallyl isocyanurate, triallyl cyanurate, and N,N'-m-phenylene-bismaleimide. Optionally, the antioxidant includes one or more of antioxidants DNP, AW, TMQ, 6PPD, 4020, RD, and BLE. The silane coupling agent selected in this application generates free radicals during compounding, which can react with the resin and elastomer to connect the resin and elastomer through covalent bonds, thereby preventing gel formation and maintaining good elasticity and extensibility of the rubber material.
[0030] This application provides a method for preparing the above-mentioned high-strength, high-toughness rubber material, the method comprising the following steps: S1. Mix 50-70 wt% of the total rubber with the profiled fiber composition, filler, silane coupling agent, stearic acid, zinc oxide and antioxidant for the first time to obtain a first-stage compound rubber. S2. Add all the remaining rubber to the first-stage compound and mix for a second time to obtain the second-stage compound. S3. The second-stage compound rubber and vulcanizing agent are mixed for a third time to obtain the final compound rubber. S4. Vulcanize the final rubber compound to obtain a high-strength, high-toughness rubber material; Optionally, the mixing temperature in steps S1 and S2 is 100~170 ℃, the mixing temperature in step S3 is 110~120 ℃, the mixing time in steps S1, S2 and S3 is 2~8 min, and the vulcanization temperature in step S4 is 130~180 ℃, the time is 10~80 min, and the pressure is 10~50 MPa.
[0031] This application provides another method for preparing the above-mentioned high-strength, high-toughness rubber material, the method comprising the following steps: 1) The profiled fiber composition, 10-30 wt% rubber, and 40-60 wt% silane coupling agent are first mixed to obtain a first-stage compound; 2) Add 40-50 wt% of the filler, remaining silane coupling agent, stearic acid, zinc oxide, antioxidant, and rubber to the first-stage compound for a second mixing to obtain the second-stage compound. 3) Add all the remaining rubber to the second-stage compound and mix for a third time to obtain the third-stage compound; 4) The three-stage compound rubber and vulcanizing agent are mixed for the fourth time to obtain the final compound rubber; 5) The final rubber compound is vulcanized to obtain high-strength, high-toughness rubber materials; Optionally, the mixing temperature in steps 1), 2), and 3) is 100~170 ℃, the mixing temperature in step 4) is 110~120 ℃, the mixing time in steps 1), 2), 3) and 4) is 2~8 min, and the vulcanization temperature in step 5) is 130~180 ℃, the time is 10~80 min, and the pressure is 10~50 MPa.
[0032] This application provides the above-mentioned high-strength, high-toughness rubber materials for use in the manufacture of tires, hoses, vibration damping components, seals, and flexible wearable components.
[0033] The beneficial effects of this application include: 1) In the present application, the rubber material can improve the strength and toughness of the rubber material by adding shaped fibers, gradient variable diameter fibers, end spherical fibers and dendritic fibers.
[0034] 2) The rubber material in this application has excellent strength and toughness. Compared with elastomer raw materials, it has better comprehensive performance in terms of tensile strength, 100% constant elongation stress, elongation at break, tear strength and resilience. It has important application scenarios in products such as tires, hoses, shock absorbers, seals and flexible wearables. Attached Figure Description
[0035] The accompanying drawings, which are included to provide a further understanding of this application and form part of this application, illustrate exemplary embodiments and are used to explain this application, but do not constitute an undue limitation of this application. In the drawings: Figure 1 This is an electron microscope image of the gradient diameter variable fiber (wave-shaped) in the rubber material of this application; Figure 2This is an electron microscope image of the gradient diameter variable fiber (tapered) in the rubber material of this application; Figure 3 This is an electron microscope image of the end-spherical fibers of this application in a rubber material; Figure 4 This is an electron microscope image of the dendritic fibers in rubber materials according to this application. Detailed Implementation
[0036] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments. Unless otherwise specified, the raw materials in the embodiments of the present application are all purchased through commercial channels.
[0037] It should be noted that this application does not specifically limit the preparation method of irregular nanofibers. For example, currently mature methods for preparing nanofibers include stretching, template method, casting method, island method, in-situ fiber formation, self-assembly method, and electrospinning. Among these methods, electrospinning has high maturity and wide applicability. It involves stretching a jet of polymer raw materials at high speed under the action of a high-voltage electrostatic field, and solidifying the fibers through phase separation during the process. The advantages of this technology are strong controllability of the spinning process, a wide range of fiber diameters, and diverse structures, making it very suitable for preparing irregular nanofibers.
[0038] As a feasible implementation method, the electrospinning process is used to prepare gradient diameter fibers, end-globose fibers, and dendritic fibers through the following steps: 1) Dissolve the shaped fiber polymer in a solvent to prepare a shaped fiber polymer solution; 2) The polymer solution of the shaped fiber is added to the injection pump of the electrospinning equipment, and the electrospinning process conditions are controlled to prepare gradient variable diameter fibers, end spherical fibers and dendritic fibers with the following morphologies; In one embodiment, the shaped fiber composition has a fiber diameter of less than 1000 nm; the gradient diameter fiber has a smooth transition in fiber diameter along the axial direction, with a fiber diameter change rate of less than 50 nm per hundred nanometers along the axial direction, and a fiber aspect ratio of 5 to 200; the end-spherical fiber includes a trunk and end-spherical sections, with the trunk aspect ratio of 5 to 200 excluding the end-spherical sections, and the diameter of the end-spherical section being 1.2 to 3 times that of the trunk; the dendritic fiber includes a trunk and branches, with the trunk aspect ratio of 10 to 200, the branch aspect ratio of 5 to 150, the length ratio of the trunk to the branches being 1 to 200, and the diameter ratio of the trunk to the branches being 1 to 20.
[0039] In one embodiment, the shaped fiber composition has a fiber diameter of less than 500 nm; the gradient diameter fiber has a smooth transition in fiber diameter along the axial direction, with a change rate of less than 50 nm per 100 nanometers along the axial direction, and a fiber aspect ratio of 5 to 200; the end-spherical fiber has a trunk aspect ratio of 5 to 200 (excluding the end-spherical part), an end-spherical diameter: trunk diameter of 1.2 to 3, a smooth transition in trunk diameter along the axial direction, and a change rate of less than 50 nm per 100 nanometers along the axial direction; the dendritic fiber has a trunk aspect ratio of 10 to 200, a branch aspect ratio of 5 to 150, a trunk-to-branch length ratio of 1 to 200, a trunk-to-branch diameter ratio of 1 to 20, a trunk-to-branch diameter ratio of 1 to 20, a trunk-to-branch diameter smooth transition along the axial direction, and a change rate of less than 50 nm per 100 nanometers along the axial direction.
[0040] As a feasible implementation method, the electrospinning process is used to prepare gradient diameter fibers, end-globose fibers, and dendritic fibers through the following steps: (1) Preparation of gradient diameter fiber S1. Preparation of polymer solution The polymer is dissolved in a corresponding good solvent / non-solvent to form a homogeneous solution with a viscosity of 100~2000 cp. The good solvent is a solvent with a polymer-solvent interaction parameter of less than 0.5. The good solvent may be one or more of amides, sulfoxides, alcohols, and acids. The non-solvent may be one or more of water, alcohols, alkanes, esters, and ketones.
[0041] S2, electrospinning A polymer solution is added to a syringe pump, and gradient-diameter fibers are ejected by dynamically controlling the pump's flow rate, receiving distance, and voltage. Under the influence of an intermittent high-frequency electric field, fibers of a certain length are produced. The spinning solution flow rate is 0.1–10 μL / min, with a dynamic control accuracy of no more than 0.05 μL / min; the receiving distance is 5–50 cm, with a dynamic linear control rate of 0.1–1 mm / s; the voltage is 5–25 kV, and the voltage is dynamically adjusted to maintain a constant electric field strength as the receiving distance changes; the high-frequency electric field frequency is 1–10 kHz, and the pulse width is 50–200 μs.
[0042] (2) Preparation of end-globose fibers S1. Preparation of polymer solution The polymer is dissolved in a suitable good solvent / non-solvent to form a homogeneous solution with a viscosity of 1500-2000 cp, which serves as the core layer solution. The polymer (PVP or PVA) is dissolved in a suitable good solvent / non-solvent to form a homogeneous solution with a viscosity of 100-500 cp, which serves as the sheath layer solution. The good solvent is a solvent with a polymer-solvent interaction parameter of less than 0.5, and can be one or more of amides, sulfoxides, alcohols, and acids. The non-solvent is one or more of water, alcohols, alkanes, esters, and ketones.
[0043] S2, electrospinning The polymer solution is added to the injection pump, the electric field voltage is pre-increased to initiate sheath pre-spraying, and then the voltage is rapidly reduced to initiate core layer spraying. To terminate spraying, sheath spraying is first stopped, and the electric field voltage is reduced. An intermittent high-frequency electric field can be applied between the injection port and the receiving device to achieve fiber preparation of a certain length. The fiber is collected and soaked in ethanol or water for 2 hours to dissolve and remove the sheath material, retaining the fiber backbone and spheres. If needed, gradient-diameter fibers with spherical ends can be sprayed by dynamically controlling the flow rate, receiving distance, and voltage of the injection pump. The spinning solution flow rate is 0.1~10 μL / min, with a dynamic control accuracy of no more than 0.05 μL / min; the start-up time interval between the sheath and core layers is 0~0.5s, the initial voltage is 15~25 KV, and the voltage decreases by 5~15 KV; when the spinning stops, the voltage decreases by 5~10 KV over a period of 0~0.5s; the receiving distance is 5~50 cm, with a dynamic linear control rate of 0.1~1 mm / s; the voltage is 5~25 KV, and the voltage is dynamically adjusted as the receiving distance changes to maintain a constant electric field strength; the high-frequency electric field frequency is 1~10 kHz, and the pulse width is 50~200 μs.
[0044] (3) Preparation of dendritic fibers S1. Preparation of polymer solution The polymer is dissolved in a suitable good solvent / non-solvent to form a homogeneous solution with a viscosity of 1500-2000 cp, which serves as the main solution; the polymer is also dissolved in a suitable good solvent / non-solvent to form a homogeneous solution with a viscosity of 100-1000 cp, which serves as the branch solution. The good solvent is a solvent with a polymer-solvent interaction parameter of less than 0.5, and can be one or more of amides, sulfoxides, alcohols, and acids. The non-solvent is one or more of water, alcohols, alkanes, esters, and ketones.
[0045] S2, electrospinning The solution jetting channel is divided into a main solution channel and branch solution channels, which are distributed in a tree-like shape with a certain angle, and the intersection is controlled by a valve. The polymer solution is added to the injection pump. First, the main solution is jetted at a certain flow rate. Then, the valve at the intersection is activated intermittently to jet the branch solution. A transverse electric field is set in the jetting nozzle and the receiving device, and a micro-template is used to collect the fibers. If needed, the flow rate of the injection pump, the receiving distance, and the voltage can be dynamically controlled to jet tree-shaped, gradient-diameter fibers. The spinning solution flow rate is 0.1~10 μL / min, with a dynamic control accuracy of no more than 0.05 μL / min; the receiving distance is 5~50 cm, with a dynamic linear control rate of 0.1~1 mm / s; the voltage is 5~25 KV, and the voltage is dynamically adjusted with changes in the receiving distance to maintain a constant electric field strength; the transverse electric field is 0.5~5 KV / cm; the micro-template can be silicon-based, and the groove spacing is controllable from 1~50 μm.
[0046] As a specific implementation method, polyhexamethylene adipamide (PA66) gradient diameter fibers are prepared using the following method: S1. Preparation of polymer solution Polyhexamethylene adipamide (PA66) was dissolved in a solvent with a formic acid:acetic acid ratio of 6:4 at a concentration of 7% to form a homogeneous solution with a viscosity of 800-1000 cp.
[0047] S2, electrospinning The polymer solution is added to the injection pump. According to the pre-programmed control program, the flow rate of the injection pump is dynamically controlled in the range of 0.4~1.2 μL / min, the receiving distance is dynamically controlled in the range of 10~15 cm, the voltage is dynamically controlled in the range of 10~18 KV, and the electric field strength is maintained at 1.2 KV / cm. During the spinning process, the fiber length is monitored in real time by a high-speed camera. When the length reaches 4.2 μm, a pulse is triggered to realize the preparation of gradient diameter fiber.
[0048] The diameter of the gradient variable diameter fiber is 50~300 nm, the diameter change rate per hundred nanometers along the axial direction is 20~40 nm, and the aspect ratio of the fiber is 20~30.
[0049] As a specific implementation method, polyhexamethylene adipamide (PA66) end-spherical fibers are prepared using the following method: S1. Preparation of polymer solution Polyhexamethylene adipamide (PA66) was dissolved in formic acid at a concentration of 9% and a viscosity of 1500-1600 cp to serve as the core layer solution; PVA was dissolved in water at a concentration of 4% and a viscosity of 300 cp to serve as the sheath layer solution.
[0050] S2, electrospinning The core and sheath solutions were added to the injection pump separately. Following a pre-programmed control procedure, sheath injection was initiated at 20 kV. After 0.3 s, core injection was initiated, reducing the sheath voltage to 8 kV and the core voltage to 12 kV. During spinning, the injection pump flow rate was dynamically controlled between 0.4 and 1.2 μL / min, the receiving distance between 10 and 15 cm, and the voltage between 8 and 12 kV. The electric field strength was maintained at 1 kV / cm. The fiber length was monitored in real-time using a high-speed camera, triggering a pulse when the fiber reached 12.2 μm to achieve fiber preparation of a specific length. At the end of spinning, sheath injection was stopped, and the core voltage was reduced to 5 kV over 0.3 s. The fibers were collected and soaked in water for 2 hours to dissolve and remove the sheath material, retaining the fiber backbone and spheres.
[0051] The diameter of the end-globose fiber backbone is 80~300 nm, the aspect ratio of the backbone is 60~70 except for the end-globose type, the diameter of the end-globose type is 1.5~2.0, and the diameter change rate of the fiber is 20~40 nm per hundred nanometers along the axial direction.
[0052] As a specific implementation method, polyhexamethylene adipamide (PA66) dendritic fibers are prepared using the following method: S1. Preparation of polymer solution Polyhexamethylene adipamide (PA66) was dissolved in a formic acid:acetic acid 7:3 solution with a concentration of 10% and a viscosity of 1500~1600 cp, as the main solution; polyhexamethylene adipamide (PA66) was dissolved in a formic acid:water 8:2 solution with a concentration of 6% and a viscosity of 700~800 cp, as the branch solution.
[0053] S2, electrospinning The main stem and branch solutions were added to the syringe pumps separately. According to the pre-programmed control procedure, the main stem solution was first sprayed at a certain flow rate. The flow rate of the syringe pump was dynamically controlled in the range of 0.4~1.2 μL / min, the receiving distance was dynamically controlled in the range of 10~15 cm, the voltage was dynamically controlled in the range of 10~18 kV, and the electric field strength was maintained at 1.2 kV / cm. The valve at the junction was intermittently activated to spray the branch solution. The flow rate of the syringe pump was 0.4 μL / min, the receiving distance was 15 cm, and the voltage was 8 kV. A transverse electric field with an electric field strength of 1.5 kV / cm was set in the spray nozzle and the receiving device. The fibers were collected using a micro-template receiver. The micro-template was silicon-based and the groove spacing was 3.7 μm.
[0054] The diameter of the dendritic fiber is 50~300 nm, the aspect ratio of the main trunk is 20~25, the aspect ratio of the branches is 10~15, the length ratio of the main trunk fiber to the branches is 5~10, the diameter ratio of the main trunk fiber to the branches is 1.5~2, and the diameter variation rate of the main trunk fiber per hundred nanometers along the axial direction is 20~40 nm.
[0055] As a specific implementation method, polyethylene terephthalate (PET) gradient diameter fibers are prepared using the following method: S1. Preparation of polymer solution Polyethylene terephthalate (PET) was dissolved in hexafluoroisopropanol (HFIP) at a concentration of 9% to form a homogeneous solution with a viscosity of 800-1000 cp.
[0056] S2, electrospinning The polymer solution is added to the injection pump. According to the pre-programmed control program, the flow rate of the injection pump is dynamically controlled in the range of 0.4~1.2 μL / min, the receiving distance is dynamically controlled in the range of 10~15 cm, the voltage is dynamically controlled in the range of 10~18 KV, and the electric field strength is maintained at 1.2 KV / cm. During the spinning process, the fiber length is monitored in real time by a high-speed camera. When the fiber length reaches 12.9 μm, a pulse is triggered to realize the preparation of gradient diameter fiber.
[0057] The diameter of the gradient variable diameter fiber is 50~300 nm, the diameter change rate of the fiber is 20~40 nm per hundred nanometers along the axial direction, and the aspect ratio of the fiber is 70~80.
[0058] As a specific implementation method, polyethylene terephthalate (PET) end-spherical fibers are prepared using the following method: S1. Preparation of polymer solution Polyethylene terephthalate (PET) was dissolved in hexafluoroisopropanol (HFIP) at a concentration of 10% and a viscosity of 1500-1600 cp to serve as the core layer solution; PVP was dissolved in water at a concentration of 5% and a viscosity of 400 cp to serve as the sheath layer solution.
[0059] S2, electrospinning The core and sheath solutions were added to the injection pump separately. Following a pre-programmed control procedure, sheath injection was initiated at 18 kV. After 0.4 s, core injection was initiated, reducing the sheath voltage to 9 kV and the core voltage to 12 kV. During spinning, the injection pump flow rate was dynamically controlled between 0.4 and 1.2 μL / min, the receiving distance between 10 and 15 cm, and the voltage between 9 and 12 kV. The electric field strength was maintained at 1 kV / cm. The fiber length was monitored in real-time using a high-speed camera, triggering a pulse when it reached 4.6 μm to achieve fiber preparation of a specific length. At the end of spinning, sheath injection was stopped, and the core voltage was reduced to 6 kV over 0.3 s. The fibers were collected and soaked in water for 2 hours to dissolve and remove the sheath material, retaining the fiber backbone and spheres.
[0060] The diameter of the end-globose fiber backbone is 80~300 nm, the aspect ratio of the backbone is 20~30 except for the end-globose type, the diameter of the end-globose type is 1.5~2.0, and the diameter change rate of the fiber is 20~40 nm per hundred nanometers along the axial direction.
[0061] As a specific implementation method, polyethylene terephthalate (PET) dendritic fibers are prepared using the following method: S1. Preparation of polymer solution Polyethylene terephthalate (PET) was dissolved in hexafluoroisopropanol (HFIP) solvent at a concentration of 10% and a viscosity of 1500-1600 cp as the main solution; polyethylene terephthalate (PET) was dissolved in hexafluoroisopropanol (HFIP) solvent at a concentration of 6% and a viscosity of 600-700 cp as the branch solution.
[0062] S2, electrospinning The main stem and branch solutions were added to the syringe pumps separately. According to the pre-programmed control procedure, the main stem solution was first sprayed at a certain flow rate. The flow rate of the syringe pump was dynamically controlled in the range of 0.4~1.2 μL / min, the receiving distance was dynamically controlled in the range of 10~15 cm, the voltage was dynamically controlled in the range of 10~18 kV, and the electric field strength was maintained at 1.2 kV / cm. The valve at the junction was intermittently activated to spray the branch solution. The flow rate of the syringe pump was 0.7 μL / min, the receiving distance was 30 cm, and the voltage was 10 kV. A transverse electric field with an electric field strength of 2.5 kV / cm was set in the spray nozzle and the receiving device. The fibers were collected using a microtemplate receiver. The microtemplate was silicon-based and the groove spacing was 12.9 μm.
[0063] The diameter of the dendritic fiber is 50~300 nm, the aspect ratio of the main trunk is 70~80, the aspect ratio of the branches is 40~50, the length ratio of the main trunk fiber to the branches is 60~70, the diameter ratio of the main trunk fiber to the branches is 5~10, and the diameter variation rate of the main trunk fiber per hundred nanometers along the axial direction is 20~40 nm.
[0064] As a specific implementation method, poly(p-phenylene terephthalamide) gradient diameter fiber is prepared using the following method: S1. Preparation of polymer solution Poly(p-phenylene terephthalamide) was dissolved in a solvent of N-methylpyrrolidone (NMP) and LiCl (5% LiCl) to form a homogeneous solution with a viscosity of 800-1000 cp.
[0065] S2, electrospinning The polymer solution is added to the injection pump. According to the pre-programmed control program, the flow rate of the injection pump is dynamically controlled in the range of 0.4~1.2 μL / min, the receiving distance is dynamically controlled in the range of 10~15 cm, the voltage is dynamically controlled in the range of 10~20 KV, and the electric field strength is maintained at 1.4 KV / cm. During the spinning process, the fiber length is monitored in real time by a high-speed camera. When the length reaches 4.2 μm, a pulse is triggered to realize the preparation of gradient diameter fiber.
[0066] The diameter of the gradient variable diameter fiber is 50~300 nm, the diameter change rate per hundred nanometers along the axial direction is 20~40 nm, and the aspect ratio of the fiber is 20~30.
[0067] As a specific implementation method, ultra-high molecular weight polyethylene gradient diameter fibers are prepared using the following method: S1. Preparation of polymer solution Ultra-high molecular weight polyethylene (UHMWPE) was dissolved in a solvent of decahydronaphthalene at a dissolution temperature of 140 °C and a concentration of 3%, forming a homogeneous solution with a viscosity of 1000~1100 cp.
[0068] S2, electrospinning The polymer solution is added to the injection pump. According to the pre-programmed control program, the flow rate of the injection pump is dynamically controlled in the range of 0.4~1.2 μL / min, the receiving distance is dynamically controlled in the range of 10~15 cm, the voltage is dynamically controlled in the range of 15~20 KV, and the electric field strength is maintained at 1.8 KV / cm. During the spinning process, the fiber length is monitored in real time by a high-speed camera. When the fiber length reaches 12.9 μm, a pulse is triggered to realize the preparation of gradient diameter fiber.
[0069] The diameter of the gradient variable diameter fiber is 50~300 nm, the diameter change rate of the fiber is 20~40 nm per hundred nanometers along the axial direction, and the aspect ratio of the fiber is 70~80.
[0070] As a specific implementation method, polyacrylonitrile gradient diameter fibers are prepared using the following method: S1. Preparation of polymer solution Polyacrylonitrile was dissolved in dimethylformamide (DMF) solvent at a concentration of 7% to form a homogeneous solution with a viscosity of 800-1000 cp.
[0071] S2, electrospinning The polymer solution is added to the injection pump. According to the pre-programmed control program, the flow rate of the injection pump is dynamically controlled in the range of 0.4~1.2 μL / min, the receiving distance is dynamically controlled in the range of 10~15 cm, the voltage is dynamically controlled in the range of 10~18 KV, and the electric field strength is maintained at 1.2 KV / cm. During the spinning process, the fiber length is monitored in real time by a high-speed camera. When the fiber length reaches 30.4 μm, a pulse is triggered to realize the preparation of gradient variable diameter fibers.
[0072] The diameter of the gradient variable diameter fiber is 50~300 nm, the diameter change rate per hundred nanometers along the axial direction is 20~40 nm, and the aspect ratio of the fiber is 170~180.
[0073] As a specific implementation method, polyester-type polyurethane gradient diameter fiber is prepared using the following method: S1. Preparation of polymer solution Polyester-type polyurethane is dissolved in N,N-dimethylformamide (DMF) solvent at a concentration of 5% to form a homogeneous solution with a viscosity of 800~1000 cp.
[0074] S2, electrospinning The polymer solution is added to the injection pump. According to the pre-programmed control program, the flow rate of the injection pump is dynamically controlled in the range of 0.4~1.4 μL / min, the receiving distance is dynamically controlled in the range of 10~18 cm, the voltage is dynamically controlled in the range of 10~18 KV, and the electric field strength is maintained at 1.2 KV / cm. During the spinning process, the fiber length is monitored in real time by a high-speed camera. When the fiber length reaches 30.4 μm, a pulse is triggered to realize the preparation of gradient diameter fiber.
[0075] The diameter of the gradient variable diameter fiber is 50~300 nm, the diameter change rate per hundred nanometers along the axial direction is 20~40 nm, and the aspect ratio of the fiber is 170~180.
[0076] As a specific implementation method, polytetrafluoroethylene gradient variable diameter fibers are prepared using the following method: S1. Preparation of polymer solution Polytetrafluoroethylene was dissolved in acetone at a concentration of 7% to form a homogeneous solution with a viscosity of 800-1000 cp.
[0077] S2, electrospinning The polymer solution is added to the injection pump. According to the pre-programmed control program, the flow rate of the injection pump is dynamically controlled in the range of 0.4~1.2 μL / min, the receiving distance is dynamically controlled in the range of 10~15 cm, the voltage is dynamically controlled in the range of 10~18 KV, and the electric field strength is maintained at 1.6 KV / cm. During the spinning process, the fiber length is monitored in real time by a high-speed camera. When the fiber length reaches 4.6 μm, a pulse is triggered to realize the preparation of gradient diameter fiber.
[0078] The diameter of the gradient variable diameter fiber is 50~300 nm, the diameter change rate per hundred nanometers along the axial direction is 20~40 nm, and the aspect ratio of the fiber is 25~30.
[0079] It should be noted that those skilled in the art can also make conventional adjustments based on the above methods to obtain gradient diameter fibers, end spherical fibers and dendritic fibers with different morphologies, and the preparation methods of gradient diameter fibers, end spherical fibers and dendritic fibers can be adjusted according to the material. Moreover, the above preparation methods are only feasible implementation methods and do not unduly limit this application.
[0080] To better illustrate the morphology, dispersion, and interfacial interactions of fibers in high-strength, high-toughness rubber materials, the illustrations in this invention use scanning electron microscopy (SEM) images of fiber morphology in rubber materials. For example... Figures 1-4 The images show the results of the fabricated gradient diameter fibers (polyacrylonitrile), gradient diameter fibers (polytetrafluoroethylene), end-spherical fibers (polyhexamethylene adipamide), and dendritic fibers (polyethylene terephthalate). It should be noted that due to the large aspect ratio of the shaped fibers, and due to imaging limitations, it is difficult to display the overall morphology of such high aspect ratio fibers when photographing their diameter. Furthermore, the scanning electron microscope images are taken to observe the distribution of shaped fibers in rubber materials. Therefore, only the key structural features of gradient diameter fibers, end-spherical fibers, and dendritic fibers are shown in the rubber materials.
[0081] The present application solution will be described below through specific embodiments.
[0082] Example 1 The rubber material comprises, by weight, 100 parts rubber, 5 parts profiled fiber composition, 55 parts carbon black, 2.0 parts silane coupling agent, 2.0 parts stearic acid, 2.0 parts zinc oxide, 2.0 parts sulfur, 2.0 parts vulcanization accelerator, and 3 parts antioxidant.
[0083] The rubber is natural rubber.
[0084] The material of the profiled fiber is polyhexamethylene adipamide (PA66), and the weight ratio of gradient variable diameter fiber, end spherical fiber and dendritic fiber is 70:15:15.
[0085] The carbon black has an average particle size of 30 nm and a DBP oil absorption value of 110 cm⁻¹. 3 / 100g; The silane coupling agent is bis(γ-triethoxysilylpropyl) disulfide; The vulcanization accelerator is N-tert-butyl-2-benzothiazole sulfenamide NS; The antioxidant is antioxidant 4020; The preparation method includes the following steps: S1. The entire shaped fiber composition, 20% rubber, and 50% silane coupling agent are mixed for the first time to obtain a compound rubber. S2. Add carbon black, the remaining silane coupling agent, stearic acid, zinc oxide, antioxidant and 45% of the total amount of rubber to the first-stage compound and perform a second mixing to obtain the second-stage compound. S3. Add all the remaining rubber to the second-stage compound and mix for a third time to obtain the third-stage compound. S4. Mix the three-stage compound rubber with sulfur and vulcanization accelerator for the fourth time to obtain the final compound rubber. S5. Vulcanize the final rubber compound to obtain a high-strength, high-toughness rubber material.
[0086] The mixing temperature in steps S1, S2, and S3 is 135 ℃, the mixing temperature in step S4 is 115 ℃, the mixing time in steps S1, S2, S3, and S4 is 5 min, and the vulcanization temperature in step S5 is 160 ℃, the time is 45 min, and the pressure is 30 MPa.
[0087] Example 2 The rubber material comprises, by weight, 100 parts rubber, 1 part profiled fiber composition, 100 parts silica, 4 parts silane coupling agent, 1 part stearic acid, 1 part zinc oxide, 0.5 parts sulfur, 0.5 parts vulcanization accelerator, and 0.5 parts antioxidant.
[0088] The rubber is butadiene-styrene copolymer rubber.
[0089] The material of the profiled fiber is polyhexamethylene adipamide (PA66), and the weight ratio of gradient variable diameter fiber, end spherical fiber and dendritic fiber is 90:5:5.
[0090] The average particle size of silica is 40 nm, and the specific surface area is 260 m². 2 / g; The silane coupling agent is bis(γ-triethoxysilylpropyl) disulfide; The vulcanization accelerator is N-tert-butyl-2-benzothiazole sulfenamide NS; The antioxidant is antioxidant 4020; The preparation method includes the following steps: S1. The entire shaped fiber composition, 10% rubber, and 40% silane coupling agent are mixed for the first time to obtain a compound rubber. S2. Add 40% of the total amount of silica, remaining silane coupling agent, stearic acid, zinc oxide, antioxidant, and rubber to the first-stage compound and perform a second mixing to obtain the second-stage compound. S3. Add all the remaining rubber to the second-stage compound and mix for a third time to obtain the third-stage compound. S4. Mix the three-stage compound rubber with sulfur and vulcanization accelerator for the fourth time to obtain the final compound rubber. S5. Vulcanize the final rubber compound to obtain a high-strength, high-toughness rubber material.
[0091] The mixing temperature in steps S1, S2, and S3 is 170 ℃, the mixing temperature in step S4 is 120 ℃, the mixing time in steps S1, S2, S3, and S4 is 2 min, and the vulcanization temperature in step S5 is 190 ℃, the time is 10 min, and the pressure is 10 MPa.
[0092] Example 3 The rubber material comprises, by weight, 100 parts rubber, 10 parts profiled fiber composition, 10 parts calcium carbonate, 0.5 parts silane coupling agent, 4.5 parts stearic acid, 4 parts zinc oxide, 2.0 parts peroxide vulcanizing agent, 1.5 parts vulcanization accelerator, and 5 parts antioxidant.
[0093] The rubber is butadiene rubber.
[0094] The material of the profiled fiber is polyhexamethylene adipamide (PA66), and the weight ratio of gradient variable diameter fiber, end spherical fiber and dendritic fiber is 50:30:20.
[0095] The average particle size of calcium carbonate is 50 nm; The silane coupling agent is bis(γ-triethoxysilylpropyl) disulfide; The peroxide vulcanizing agent is dicumyl peroxide. The vulcanization accelerator is triallyl isocyanurate (TAIC); The antioxidant is antioxidant 4020; The preparation method includes the following steps: S1. The entire shaped fiber composition, 30% rubber, and 60% silane coupling agent are mixed for the first time to obtain a compound rubber. S2. Add calcium carbonate, the remaining silane coupling agent, stearic acid, zinc oxide, antioxidant and 50% of the total amount of rubber to the first-stage compound and perform a second mixing to obtain the second-stage compound. S3. Add all the remaining rubber to the second-stage compound and mix for a third time to obtain the third-stage compound. S4. Mix the three-stage compound rubber with the vulcanizing agent and vulcanization accelerator for the fourth time to obtain the final compound rubber. S5. Vulcanize the final rubber compound to obtain a high-strength, high-toughness rubber material.
[0096] The mixing temperature in steps S1, S2, and S3 is 100 ℃, the mixing temperature in step S4 is 110 ℃, the mixing time in steps S1, S2, S3, and S4 is 8 min, and the vulcanization temperature in step S5 is 130 ℃, the time is 80 min, and the pressure is 50 MPa.
[0097] Example 4 The difference from Example 1 is that the rubber is isoprene rubber, the material of the profiled fiber is polyethylene terephthalate (PET), the filler is nano-kaolin, the vulcanization accelerator is guanidine vulcanization accelerator DPG, the antioxidant is antioxidant 6PPD, and the silane coupling agent is γ-mercaptopropyltrimethoxysilane.
[0098] Example 5 The difference from Example 1 is that the rubber is PVC, the gradient diameter fiber in the profiled fiber is poly(p-phenylene terephthalamide), the end spherical fiber and the dendritic fiber are poly(hexamethylene adipamide) (PA66), the filler is nano-wollastonite powder, the silane coupling agent is bis(γ-triethoxysilylpropyl)tetrasulfide, the vulcanization accelerator is N-cyclohexyl-2-benzothiazole sulfenamide, and the antioxidant is antioxidant AW.
[0099] Example 6 The difference from Example 1 is that the rubber is butyl rubber, the gradient diameter fiber in the profiled fiber is made of ultra-high molecular weight polyethylene, the end spherical fiber and the dendritic fiber are made of polyhexamethylene adipamide (PA66), the vulcanizing agent is dicumyl peroxide, the vulcanization accelerator is triallyl cyanurate, and the antioxidant is BLE.
[0100] Example 7 The difference from Example 1 is that the rubber is ethylene propylene rubber, the gradient diameter fiber in the profiled fiber is made of polyacrylonitrile, the end spherical fiber and the dendritic fiber are made of polyethylene terephthalate (PET), and the silane coupling agent is γ-mercaptopropyl (bis-(tetrazyl-hexaethoxy)ethoxy)silane.
[0101] Example 8 The difference from Example 1 is that the gradient diameter fiber in the profiled fiber is made of polyester polyurethane, the end spherical fiber and the dendritic fiber are made of polyethylene terephthalate (PET), and the silane coupling agent is 3-octanoylthio-1-propyltriethoxysilane.
[0102] Example 9 The difference from Example 1 is that the gradient diameter fiber in the profiled fiber is made of polytetrafluoroethylene, and the end spherical fiber and dendritic fiber are made of polyethylene terephthalate (PET).
[0103] Example 10 The difference from Example 1 is that the weight ratio of gradient variable diameter fiber, end spherical fiber and dendritic fiber is 60:20:20.
[0104] Example 11 The difference from Example 1 is that the weight ratio of gradient variable diameter fiber, end spherical fiber and dendritic fiber is 80:10:10.
[0105] Example 12 The difference from Example 1 is that the weight ratio of gradient variable diameter fiber, end spherical fiber and dendritic fiber is 40:40:20.
[0106] Example 13 The difference from Example 1 is that the weight ratio of gradient variable diameter fiber, end spherical fiber and dendritic fiber is 40:30:30.
[0107] Example 14 The difference from Example 1 is that the weight ratio of gradient variable diameter fiber, end spherical fiber and dendritic fiber is 95:3:2.
[0108] Example 15 The difference from Example 1 is that it contains only gradient diameter fibers.
[0109] Example 16 The difference from Example 1 is that it contains only end-spherical fibers.
[0110] Example 17 The difference from Example 1 is that it contains only dendritic fibers.
[0111] Example 18 The difference from Example 1 is that the aspect ratio of the gradient variable diameter fiber is 200~220; the aspect ratio of the main stem of the end spherical fiber is 200~220; and the aspect ratio of the main stem of the dendritic fiber is 200~220, while the aspect ratio of the branches is 150~160.
[0112] Example 19 The difference from Example 1 is that the aspect ratio of the gradient variable diameter fiber is 300~320; the aspect ratio of the main stem of the end spherical fiber is 300~320; and the aspect ratio of the main stem of the dendritic fiber is 300~320, while the aspect ratio of the branches is 200~210.
[0113] Comparative Example 1 The difference from Example 1 is that the rubber includes only natural rubber and does not contain the shaped fiber composition.
[0114] Comparative Example 2 The difference from Example 1 is that the rubber consists only of butadiene-styrene copolymer rubber and does not contain the shaped fiber composition.
[0115] Comparative Example 3 The difference from Example 1 is that the rubber consists only of butadiene rubber and does not contain the profiled fiber composition. Comparative Example 4 The difference from Example 1 is that the rubber only includes isoprene rubber and does not contain the profiled fiber composition.
[0116] Comparative Example 5 The difference from Example 1 is that the rubber consists only of butyl ester rubber and does not contain the shaped fiber composition.
[0117] Comparative Example 6 The difference from Example 1 is that the rubber consists only of butyl rubber and does not contain the shaped fiber composition.
[0118] Comparative Example 7 The difference from Example 1 is that the rubber consists only of ethylene propylene rubber and does not contain the shaped fiber composition.
[0119] The rubber materials prepared in the examples and comparative examples were subjected to performance tests, including tensile strength, stress at 100% elongation, elongation at break, tear strength, and resilience. The mechanical property tests were conducted according to GB / T528-2009, "Determination of Tensile Stress-Strain Properties of Vulcanized Rubber or Thermoplastic Rubber," at room temperature. The tear strength test was conducted according to GB / T529-2008, "Determination of Tear Strength of Vulcanized Rubber or Thermoplastic Rubber," at room temperature. The resilience test was conducted according to GB / T 1681-2009, "Determination of Resilience of Vulcanized Rubber," at room temperature. The test results are shown in Table 1 below.
[0120] Table 1 Test results of rubber material properties
[0121] As shown in Table 1, the rubber material in this application can improve its strength and toughness by incorporating shaped fibers, including gradient diameter fibers, end spherical fibers, and dendritic fibers.
[0122] According to the results of the embodiments and comparative examples 1 to 7, the addition of three different types of profiled fibers in this application can improve the strength and toughness of the elastomer raw materials, and the addition of profiled fibers of different materials all have good improvement effects.
[0123] According to the results of Examples 10-17, the three different types of profiled fibers added in this application have a good effect on improving the strength and fracture toughness of rubber materials at a specific ratio range. It is difficult to achieve good comprehensive performance by using only one type of profiled fiber.
[0124] As can be seen from the results of Examples 18-19, the morphology of the profiled fiber has a significant impact on the improvement of performance.
[0125] The above description is merely an embodiment of this application, and the scope of protection of this application is not limited to these specific embodiments, but is determined by the claims of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the technical concept and principles of this application should be included within the scope of protection of this application.
Claims
1. A profiled fiber-reinforced and toughened elastomer material, characterized in that, Included by weight parts: (a) 100 parts elastomer; (b) 1 to 10 parts of a profiled fiber composition, wherein the profiled fiber composition comprises one or more of gradient diameter fibers, end-spherical fibers, and dendritic fibers, and the profiled fiber composition is dispersed in the elastomer; (c) 0.5 to 4 parts of silane coupling agent; (d) 10~100 parts of filler; (e) 3 to 15 parts of a vulcanizing composition, said vulcanizing composition comprising a vulcanizing agent, a vulcanization accelerator, stearic acid and zinc oxide; (f) 0.5 to 5 parts of anti-aging agent.
2. The profiled fiber reinforced and toughened elastomer material according to claim 1, characterized in that, The fiber diameter of the irregular fiber composition is less than 1000 nm; The gradient diameter fiber has a smooth transition in fiber diameter along the axial direction, with a fiber diameter change rate of less than 50 nm per hundred nanometers along the axial direction, and a fiber aspect ratio of 5 to 200. The end-spherical fiber includes a main stem and end spherical parts. The aspect ratio of the main stem (excluding the end spherical parts) is 5~200, and the diameter of the end spherical parts is 1.2~3 times the diameter of the main stem. The dendritic fiber includes a trunk and branches, with the trunk having a length-to-diameter ratio of 10 to 200, the branches having a length-to-diameter ratio of 5 to 150, the length ratio of the trunk to the branches being 1 to 200, and the diameter ratio of the trunk to the branches being 1 to 20.
3. The shaped fiber reinforced and toughened elastomer material according to claim 1 or 2, characterized in that, The fiber diameter of the shaped fiber composition is less than 500 nm; The gradient diameter fiber has a smooth transition in fiber diameter along the axial direction, with a fiber diameter change rate of less than 50 nm per hundred nanometers along the axial direction, and a fiber aspect ratio of 5 to 200. The aspect ratio of the main stem of the end-spherical fiber, excluding the end-spherical shape, is 5~200. The diameter of the end-spherical fiber is 1.2~3 times that of the main stem. The diameter of the main stem changes smoothly along the axial direction, and the change rate of the main stem diameter within every hundred nanometers along the axial direction is less than 50nm. The dendritic fiber has a trunk aspect ratio of 10-200, a branch aspect ratio of 5-150, a trunk-to-branch length ratio of 1-200, a trunk-to-branch diameter ratio of 1-20, a trunk-to-branch diameter ratio of 1-20, a trunk diameter that smoothly transitions along the axial direction, and a trunk diameter that varies less than 50 nm per hundred nanometers along the axial direction.
4. The profiled fiber reinforced and toughened elastomer material according to claim 1, characterized in that, The gradient diameter fiber accounts for 50% to 90 wt% of the total amount of the profiled fiber composition; Optionally, the gradient diameter fiber accounts for 60% to 80 wt% of the total amount of the profiled fiber composition.
5. The shaped fiber reinforced and toughened elastomer material according to claim 1, characterized in that, The material of the profiled fiber is one or more of the following: poly(p-phenylene terephthalamide) fiber, polyimide fiber, polyester fiber, polyurethane fiber, poly(m-phenylene isophthalamide) fiber, polyolefin fiber, polyamide fiber, polyacrylonitrile fiber, polyvinyl alcohol formal fiber, polyvinyl chloride fiber, polybenzimidazole fiber, and polytetrafluoroethylene fiber. The polyester fiber includes one or more of polyethylene terephthalate fiber, polybutylene terephthalate fiber, polypropylene terephthalate fiber, and polyethylene naphthalate fiber; The polyurethane fiber includes one or more of polyether polyurethane fiber and polyester polyurethane fiber; The polyolefin fibers include one or more of the following: polyethylene fibers, ultra-high molecular weight polyethylene fibers, polypropylene fibers, poly-1-butene fibers, and halogenated homopolymer / copolymer / halogenated copolymer fibers of ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, and 4-methyl-1-pentene monomers. The polyamide fiber includes one or more of the following: polycaprolactam fiber, polyhexamethylene adipamide fiber, polydecanoyl decanoyl diamine fiber, polydecanoyl hexamethylene adipamide fiber, polydodecanoyl hexamethylene adipamide fiber, polyundecanoyl lactam fiber, polydodecanoamide fiber, and polyadipamide butylene adipamide fiber.
6. The shaped fiber reinforced and toughened elastomer material according to claim 1, characterized in that, The elastomer includes one or more of the following: natural rubber, isoprene rubber, styrene-butadiene rubber, pentadiene rubber, cis-butadiene rubber, butyl rubber, ethylene propylene rubber, fluororubber, acrylate rubber, chlorosulfonated polyethylene, silicone rubber, polyurethane rubber, polyether rubber, and polysulfide rubber. Optionally, the elastomer includes one or more of natural rubber, isoprene rubber, styrene-butadiene rubber, pentadiene rubber, butadiene rubber, cis-butadiene rubber, butyl rubber, and ethylene propylene rubber.
7. The shaped fiber reinforced and toughened elastomer material according to claim 1, characterized in that, The silane coupling agent includes one or more of vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane, γ-mercaptopropyltrimethoxysilane, bis(γ-triethoxysilylpropyl)tetrasulfide, bis(γ-triethoxysilylpropyl)disulfide, γ-mercaptopropyl(bis-(tridecyl-hexaethoxy)ethoxy)silane, and 3-octanoylthio-1-propyltriethoxysilane; The filler is selected from one or more of carbon black, silica, calcium carbonate, talc, kaolin, bentonite, mica, and wollastonite. In the vulcanization composition, the vulcanizing agent is selected from one or more of sulfur, metal oxide vulcanizing agents, or peroxide vulcanizing agents; the vulcanization accelerator is selected from one or more of dithiocarbamate vulcanization accelerators, thiuram vulcanization accelerators, thiazole vulcanization accelerators, guanidine vulcanization accelerators, sulfonamide vulcanization accelerators, triallyl isocyanurate, triallyl cyanurate, and N,N'-m-phenylene-bismaleimide. The antioxidants include one or more of the following: antioxidant DNP, antioxidant AW, antioxidant TMQ, antioxidant 6PPD, antioxidant 4020, antioxidant RD, and antioxidant BLE.
8. The method for preparing the profiled fiber reinforced and toughened elastomer material according to any one of claims 1 to 7, characterized in that, The method includes the following steps: S1. Mix 50-70 wt% of the total rubber with the profiled fiber composition, filler, silane coupling agent, stearic acid, zinc oxide and antioxidant for the first time to obtain a first-stage compound rubber. S2. Add all the remaining rubber to the first-stage compound and mix for a second time to obtain the second-stage compound. S3. The second-stage compound rubber and vulcanizing agent are mixed for a third time to obtain the final compound rubber. S4. Vulcanize the final rubber compound to obtain a high-strength, high-toughness rubber material; Optionally, the mixing temperature in steps S1 and S2 is 100~170 ℃, the mixing temperature in step S3 is 110~120 ℃, the mixing time in steps S1, S2 and S3 is 2~8 min, and the vulcanization temperature in step S4 is 130~180 ℃, the time is 10~80 min, and the pressure is 10~50 MPa.
9. The method for preparing the profiled fiber reinforced and toughened elastic material according to any one of claims 1 to 7, characterized in that, The method includes the following steps: 1) The profiled fiber composition, 10-30 wt% rubber, and 40-60 wt% silane coupling agent are first mixed to obtain a first-stage compound; 2) Add 40-50 wt% of the filler, remaining silane coupling agent, stearic acid, zinc oxide, antioxidant, and rubber to the first-stage compound for a second mixing to obtain the second-stage compound. 3) Add all the remaining rubber to the second-stage compound and mix for a third time to obtain the third-stage compound; 4) The three-stage compound rubber and vulcanizing agent are mixed for the fourth time to obtain the final compound rubber; 5) The final rubber compound is vulcanized to obtain high-strength, high-toughness rubber materials; Optionally, the mixing temperature in steps 1), 2), and 3) is 100~170 ℃, the mixing temperature in step 4) is 110~120 ℃, the mixing time in steps 1), 2), 3) and 4) is 2~8 min, and the vulcanization temperature in step 5) is 130~180 ℃, the time is 10~80 min, and the pressure is 10~50 MPa.
10. The high-strength, high-toughness rubber material as described in any one of claims 1 to 7 is used in the manufacture of tires, hoses, vibration damping components, seals, and flexible wearable components.